Efisiensi Pemasaran Produk Mie Sagu Pada Usaha Mie Sehat Cempaka - Huliselan, Hlouke A; Timisela, Natelda R; Leatemia, Ester D (Universitas Pattimura, 2024)
This research aimed to assess the marketing efficiency of sago noodle products within the Cempaka Healthy Noodle business. The findings reveal two distinct marketing channels to promote Cempaka sago noodle products. In marketing channel I, which involves the process from manufacturers to distributors and ultimately to consumers, the manufacturer (Mie Sehat Cempaka) receives varying margins, precisely 76.92% for Titi Original Noodle products, 80% for Kwetiauw Noodle products, 74.07% for Kwantung Noodle products, 74.07% for Sago Noodle products, and 71.43% for Carrot Noodle products. On the other hand, marketing channel II represents a direct route from manufacturers to consumers without intermediaries, resulting in the manufacturer (Mie Sehat Cempaka) obtaining a 100% margin for sago noodle products (Mie Titi Original, Mie Kwetiauw, Mie Kwantung, Mie Sagu, Mie Wortel). Based on the analysis of marketing margins and farmers' share, it can be concluded that supply chain channel II is more efficient than supply chain channel I. This implies that shorter supply chain channels are more efficient than longer ones.